PENGARUH MODEL PEMBELAJARAN DISCOVERY TERBIMBING TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN IPA SD - Regosiasi, Regosiasi; Rosnita, Rosnita; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aims to test the average of learning outcomes of students who are taught and without being taught by using guided discovery learning model, whether or not influence influence the use of guided discovery learning model on student learning outcomes in the subject of Natural Science in Class IV Primary School Negeri 26 Pontianak Tenggara. The research method used is experimental with the form of quantitative research. The sample of this research is the students of class IV A and IV B Primary School 26 Pontianak Southeast. Data collection techniques used are direct observation techniques and measurement techniques. Data collection tool used is the test of student learning outcomes in the form of multiple choice amounted to 40 questions. Based on the result of the research, the average of students' learning outcomes in the control class is 73,67. While the average student learning outcomes in the experimental class of 80.94. The result of hypothesis test (t-test) using t-test separated variance obtained tcount 4,6379 and ttable (Î± = 5% and dk = 47) equal to 1.67945 indicate that tcount is bigger than ttable then Ha is accepted. This means that there are differences in learning outcomes between students taught by using guided discovery learning models with students taught without using guided discovery learning models. From the calculation effect size (ES), obtained 0.93 (high criteria). The guided discovery learning model gives a high influence on the students' learning outcomes in the Natural Science lesson in the fourth grade of Public Primary School 26 Pontianak Tenggara.Â Keywords: Learning Guided Learning Model, student learning outcomes, natural science.Â